Decay resistance of some fast growing pioneer wood species of Sarawak - Dayang Filidia, binti Abang Ahmad Bolhassan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Decay resistance of fast growing pioneer wood species in Malaysia is still unknown due to lack of studies on them. Pioneer species trees can be utilize if its wood properties are known. Decay resistance is among the properties that need to be evaluated before proper utilization of fast growing pioneer species can be realized. The purpose of this study was to determine the decay resistance of some Sarawak' pioneer wood species based on weight loss, which was assessed by a modified ASTM soil block te t. Three fast growing pioneer species were selected, namely Duabanga moluccana, Dyera polyphylla and Endospermum diadenum. Hevea brasiliensis was used as control. The wood samples were Cllt into cubes of 19 mm. Cubes were exposed to three test fungi consist of two brown rot fungi, Ganoderma lucidum and Lenlinus sajorcaju, and one white rot fungus, Schizophyllum commune for six week. Average weight loss of all the woods were higher than 10% with Dyera polyphylla showed highest weight loss, 18.48% with Ganoderma lucidum, 15.20% with Lenlinus sajorcaju and 14.13% with Schizophyllum commune, while Endospermum diadenum at 14.16% with Ganoderma lucidum, 12.97% with Lenlinus sajorcaju and 13.14% with Schizophyllum commune, the least between the pioneer woods. Generally Duabanga moluccana and Endospermum diadenum have similar weight loss and this weight loss are lower than Dyera polyphylla . This study showed that the fast growing pioneer species wood of Duabanga moluccana, Dyera polyphylla and Endospermum diadenum are non-durable timber .